WAR, PEACE OR NEUTRALITY: AN OVERVIEW OF ISLAMIC POLITY’S BASIS OF INTER-STATE RELATIONS - Hassan, Muhammad Haniff (Journal of Al-Tamaddun, 2012)
There is an increase interest on Islam in the field of international relations. The paper seeks to offer an overview to the basis of inter state relations between a Muslim polity and other Muslim or non-Muslim polity. It presents three possible options that will be the basis of international relations for an Islamic polity; war, peace and neutrality. It then argues that peace is the original basis and rejects the idea of perpetual war between Islamic and non-Islamic polity as espoused by jihadist groups.